Use of Multivariable Mendelian Randomization to Address Biases Due to Competing Risk Before Recruitment - Schooling, C. M.; Lopez, P. M.; Yang, Z.; Zhao, J. V.; Au Yeung, Shiu Lun; Huang, Jian V. (Frontiers in Genetics, 2021)
Background: Mendelian randomization (MR) provides unconfounded estimates. MR is open to selection bias when the underlying sample is selected on surviving to recruitment on the genetically instrumented exposure and competing risk of the outcome. Few methods to address this bias exist. Methods: We show this selection bias can sometimes be addressed by adjusting for common causes of survival and outcome. We use multivariable MR to obtain a corrected MR estimate for statins on stroke. Statins affect survival and stroke typically occurs later in life than ischemic heart disease, making estimates for stroke open to bias from competing risk. Results: In univariable MR in the UK Biobank genetically instrumented statins did not protect against stroke (odds ratio (OR) 1.33, 95% confidence interval (CI) 0.80 to 2.20), but did in multivariable MR (OR 0.81, 95% CI 0.68 to 0.98) adjusted for major causes of survival and stroke (blood pressure, body mass index and smoking initiation) with a multivariable Q-statistic indicating absence of selection bias. However, the MR estimate for statins on stroke using MEGASTROKE remained positive and the Q statistic indicated pleiotropy. Conclusion: MR studies of harmful exposures on late onset diseases with shared etiology need to be conceptualized within a mechanistic understanding so as to identify any potential bias due to survival to recruitment on both genetically instrumented exposure and competing risk of the outcome, which may then be investigated using multivariable MR or estimated analytically and results interpreted accordingly.